2011
DOI: 10.1016/j.immuni.2011.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine Transforming Growth Factor-β1 Promotes In Vivo Th17 Cell Differentiation

Abstract: Summary TGFβ1 is a regulatory cytokine that has an important role in controlling T cell differentiation. T cell-produced TGFβ1 acts on T cells to promote Th17 cell differentiation and the development of experimental autoimmune encephalomyelitis (EAE). However, the exact TGFβ1-producing T cell subset required for Th17 cell generation and its cellular mechanism of action remain unknown. Here we showed that deletion of the Tgfb1 gene from activated T cells and Treg cells, but not Treg cells alone, abrogated Th17 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
202
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(212 citation statements)
references
References 51 publications
8
202
1
1
Order By: Relevance
“…Ablation of TGF-β1 production by CD11c + cells, however, did not completely inhibit S. pyogenes-induced Th17 formation, indicating that other cells of hematopoietic origin are involved. CD4 + T cells, perhaps regulatory T cells, were good candidates based on work in the EAE model (17). Nonetheless, S. pyogenes p:MHCII-specific naive CD4 + T cells did not become Foxp3 + regulatory T cells during S. pyogenes inoculation, and we found no role for TGF-β1 production by CD4 + T cells in S. pyogenes-driven Th17 differentiation.…”
Section: Discussionmentioning
confidence: 60%
“…Ablation of TGF-β1 production by CD11c + cells, however, did not completely inhibit S. pyogenes-induced Th17 formation, indicating that other cells of hematopoietic origin are involved. CD4 + T cells, perhaps regulatory T cells, were good candidates based on work in the EAE model (17). Nonetheless, S. pyogenes p:MHCII-specific naive CD4 + T cells did not become Foxp3 + regulatory T cells during S. pyogenes inoculation, and we found no role for TGF-β1 production by CD4 + T cells in S. pyogenes-driven Th17 differentiation.…”
Section: Discussionmentioning
confidence: 60%
“…TGF-b also regulates Th17-cell differentiation (Bettelli et al 2006;Veldhoen et al 2006a;Li et al 2007;Manel et al 2008;Yang et al 2008;Gutcher et al 2011). Th17 cells express the lineage-specific transcription factor RAR (retinoic acid receptor)-related orphan receptor C (RORC) in humans (and RORgt in mice) and produce many cytokines, including IL-17A, IL-17F, IL-21, IL-22, and granulocyte-macrophage colony-stimulating factor (GM-CSF) (Ivanov et al 2006;Korn et al 2009).…”
Section: Peripheral Homeostasismentioning
confidence: 99%
“…However, despite the indication that autocrine TGF-b signaling promotes TGF-b production in DCs, whether DCs represent the critical source of TGF-b for pTreg-cell differentiation, as proposed (Kashiwagi et al 2015), remains to be validated by genetic methods, for example, using CD11c-Cre-mediated deletion of floxed Tgfb1. Indeed, it has been shown that T cells themselves are the essential source of TGF-b for Th17 differentiation Gutcher et al 2011). …”
Section: Regulation Of Immunity By Tgf-bmentioning
confidence: 99%
See 1 more Smart Citation
“…Together, they induce RORγt, the characteristic transcription factor of the Th17 lineage, in a STAT3-dependent manner (9,46). Moreover, in the presence of IL-6, Th17 cells can secrete TGF-β in an autocrine manner thus contributing to a stable and maintained Th17 response (67). The absolute requirement for TGF-β is attributable to the inhibition of Th1 cell differentiation, since Th1 cells strongly inhibit Th17 differentiation in the absence of TGF-β (62).…”
Section: Th17 Subsetmentioning
confidence: 99%